RESEARCH OF MULTIMODAL PERCEPTION PROFILE AMONG STUDENTS - T. N. Bandurka (Acta Biomedica Scientifica)
The topicality of the research of polimodal research profile among students is determined by the necessity of studying the characteristics of students' sense perception. Revealing the peculiarities of polimodal perception among students and taking into considerations these peculiarities may solve the problem how to optimize studying process of future psychologists. Studying the peculiarities of polimodal perception will let us control the students' sense perception while teaching. The author's theoretical model of polymodal perception gave ground to create the methodology of identifying eight peculiarities in polimodal perception. The data gathered help us conclude that polimodal perception in the group of students-respondents from different regions of the country doesn't differ statistically. It may lead to the conclusion that students - future psychologists of Moscow psychological-pedagogical university and Irkutsk State University belong to the same general group, therefore in the research we will see them as one group. Studying group tendencies in polimodal perception among students shows that one cannot claim visual perception dominant type of perception. Respondents prefer to use visual and also osmatic, gustatory and gaptic modalities. Kinesthetic modality, perception of people and nature have scores lower that the average figure among other modalities chosen by students-respondents who live in Moscow and Irkutsk. These types of perception are resourceful but less recognized and demand further development. The results of the research give us the opportunity to set out ways of developing polimodal perception, correcting less recognized perception modalities among students, future psychologists.